Position Sensing with a Compact 0.1 THz Amplitude Modulated Source - Tadej Krmac; Andrej Švigelj; Janez Trontelj (Applied Sciences, 2022)
Position determination is an important manufacturing process in many modern industries. The objective of this paper is to present an affordable measurement system that can replace optical position measurement with a laser beam in an opaque environment that prevents the laser beam from penetrating through the fog of gases or other materials that are opaque to optical light. THz waves are a good example of replacing a laser beam, as shown in this article. It is known that THz rays can penetrate fabrics, wood, Styrofoam, etc. The triangulation method using an amplitude modulated THz source proved to be a cost-effective solution for position determination in opaque environments.